2013
DOI: 10.1111/neup.12061
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to an organophosphate pesticide, individually or in combination with other Gulf War agents, impairs synaptic integrity and neuronal differentiation, and is accompanied by subtle microvascular injury in a mouse model of Gulf War agent exposure

Abstract: Gulf War illness (GWI) is a currently untreatable multi-symptom disorder experienced by 1990-1991 Persian Gulf War (GW) veterans. The characteristic hallmarks of GWI include cognitive dysfunction, tremors, migraine, and psychological disturbances such as depression and anxiety. Meta-analyses of epidemiological studies have consistently linked these symptomatic profiles to the combined exposure of GW agents such as organophosphate-based and pyrethroid-based pesticides (e.g. chlorpyrifos (CPF) and permethrin (PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
58
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 50 publications
8
58
1
Order By: Relevance
“…The role pf PB in in causing neuroinflammation is unclear. Though GW-chemical exposure that included PB caused astrocytic activation and ICAM-1 increase a firm mechanistic argument in favor of the neuroinflammatory pathology is lacking[7]. [10, 68].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role pf PB in in causing neuroinflammation is unclear. Though GW-chemical exposure that included PB caused astrocytic activation and ICAM-1 increase a firm mechanistic argument in favor of the neuroinflammatory pathology is lacking[7]. [10, 68].…”
Section: Discussionmentioning
confidence: 99%
“…Mice were exposed to gulf war chemicals based on established rodent models of Gulf War Illness with some modifications[7, 10]. The treated mice group (GW-T) and TLR4 KO (GW-TLR4 KO) mice group were dosed tri-weekly for one week with PB (2mg/kg) and Permethrin.…”
Section: Methodsmentioning
confidence: 99%
“…There are concerns about the potential health effects of the many environmental exposures during the Gulf War, including oil well fire smoke, nerve agents (sarin and cyclosarin), multiple vaccinations, pyridostigmine bromide, pesticides, and depleted uranium [7,9,10,13-15]. Both human (Gulf War veteran populations) and animal studies have reported neurological outcomes associated with the exposures present during Gulf War deployment, including neuro-inflammation [16], changes in brain volume [17], hippocampal dysfunction [18,19], decreased white matter [7,9,20] and alterations in executive function and cognition [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Toxins such as lead, methylmercury, organophosphates, and arsenic have been associated with psychiatric disorders, including depression, in a number of epidemiological studies (Zierold et al, 2004; Sen and Sarathi Biswas, 2012; Beard et al, 2013; Freire and Koifman, 2013; Malekirad et al, 2013; Ojo et al, 2014; Weisskopf et al, 2013). Yet, the impact of environmental factors, particularly toxins, on the susceptibility to depression has not been investigated in great detail.…”
Section: Discussionmentioning
confidence: 99%